1998
DOI: 10.1046/j.1472-765x.1998.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant mediated interactions between Pseudomonas fluorescens, Rhizobium leguminosarum and arbuscular mycorrhizae on pea

Abstract: G . A ND R AD E, F .A .A . M. DE L EI J A N D J .M . LY NC H . 1998. Using undisturbed sandy loam soil cores heavily infested with mycorrhizae, the effects of the antibiotic-producing Pseudomonas fluorescens strain F113 and its non-antibiotic derivative Ps. fluorescens F113G22 on nodulation by introduced and indigenous Rhizobium were studied. Furthermore, the effects of the different microbial inocula on the colonization of the pea roots by mycorrhizae were studied. It was found that Ps. fluorescens F113 enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 33 publications
1
23
0
2
Order By: Relevance
“…PGPR1, PGPR2 and PGPR4 containing ACC deaminase activity significantly enhanced the pod yi eld (23-26, 24-28 a nd 18-24%, (Malik and Sindhu, 2011). In other studies also, mostly synergistic effects have been observed on nodulation and plan t growth of l egumes by mixed inoculation of B. japonicum and PGPR in soybean (Li and Alexander, 1988;Masciarelli et al, 2014), R. leguminosarum with an antibiotic-producing P. fluorescens strain F113 in pea (Andrade et al, 1998) and Bradyrhizobium/Mesorhizobium strains with Pseudomonas sp. in green gram and chickpea (Sindhu et al, 1999;.…”
Section: Coinoculation Of Selected Rhizobacterial Isolates Withmentioning
confidence: 83%
“…PGPR1, PGPR2 and PGPR4 containing ACC deaminase activity significantly enhanced the pod yi eld (23-26, 24-28 a nd 18-24%, (Malik and Sindhu, 2011). In other studies also, mostly synergistic effects have been observed on nodulation and plan t growth of l egumes by mixed inoculation of B. japonicum and PGPR in soybean (Li and Alexander, 1988;Masciarelli et al, 2014), R. leguminosarum with an antibiotic-producing P. fluorescens strain F113 in pea (Andrade et al, 1998) and Bradyrhizobium/Mesorhizobium strains with Pseudomonas sp. in green gram and chickpea (Sindhu et al, 1999;.…”
Section: Coinoculation Of Selected Rhizobacterial Isolates Withmentioning
confidence: 83%
“…E-mail: martinmartines@onda.com.br, denisdiaboloiro@bol.br, leopoldo@ffalm.br, mavanzi@bol.com.br, andradeg@uel.br Bactérias do solo, especificamente bactérias rizosféricas, podem ser eficientes no controle de doenças causadas por fungos fitopatogênicos (Oedjijono & Dragar, 1993;Andrade et al, 1998). Na avaliação dos grupos funcionais de microrganismos da rizosfera de Drosera villosa var.…”
Section: Fungistatic Effect Of Bacillus Thuringiensis and Of Other Baunclassified
“…The effects of PGPR co-inoculation on legume symbioses include increases in nodule number and/ or nodule weight, and in some cases an enhancement of nitrogen fixation or N accumulation. A variety of mechanisms have been proposed for the observed responses of symbiotic legumes to PGPR coinoculation including phytohormonal stimulation of root growth (Vessey and Buss 2002), increased production of nod gene products inducing flavonoids by the legume host (Andrade et al 1998), stimulation of root hair development (Lucas Garcia et al 2004) and secretion of B vitamins by the PGPR enhancing rhizobial growth in the rhizosphere (Marek-Kozaczuk and Skorupska 2001). Of particular interest to PGPR enhancing nodulation is the production of the phytohormone indole acetic acid (IAA).…”
Section: Introductionmentioning
confidence: 99%